Spatially segregated feedforward and feedback neurons support differential odor processing in the lateral entorhinal cortex - Leitner, Frauke C.; Melzer, Sarah; Lütcke, Henry; Pinna, Roberta; Seeburg, Peter H.; Helmchen, Fritjof; Monyer, Hannah (Nature neuroscience, 2016)
The lateral entorhinal cortex computes and transfers olfactory information from the olfactory bulb to the hippocampus and supports associative multimodal memories. Leitner et al. characterize the activity of odor-responsive cell types in this brain area and identify upstream and downstream brain areas to which olfactory information is conveyed.